The Role of Youth in Tourism Awareness Movement in West Detusoko Tourism Village, Ende Regency - Adja Mosa, Yohanes A (Universitas Pendidikan Indonesia (UPI), 2024)
This study investigates the pivotal role of local youth in promoting tourism awareness in Detusoko Barat Village, located within the Detusoko District of Ende Regency, framed by the principles of Sapta Pesona. The primary objective of this research is to elucidate the contributions and involvement of youth in fostering a conscious tourism movement within the community. Employing a descriptive qualitative research design, the study utilizes purposive sampling to identify participants, drawing from a diverse pool of local youth. Data collection methods included observations, in-depth interviews, literature reviews, and documentation, engaging seven informants to gain comprehensive insights into their experiences and perspectives. The findings indicate that while the youth in Detusoko Barat are positioned as vital agents of change and development within the context of tourism, their roles in advancing the tourism awareness movement—anchored in the Sapta Pesona framework—are not being fully realized. The research highlights gaps in engagement, suggesting that further efforts are needed to empower youth and optimize their contributions to tourism development. Ultimately, this study underscores the importance of actively involving local youth in tourism initiatives and advocates for strategies that can enhance their roles, thereby promoting a more robust and conscious tourism culture in Detusoko Barat Village.